A Note on Boardroom Challenge, Board Effectiveness and Corporate Stewardship During COVID-19. Issue 2 (June 2021) - Kaur, Manmeet; Malik, Kunjana; Sharma, Sakshi
The global COVID-19 pandemic has led to spawning norms in all quarters, including the corporate boardrooms. The transformation required in boards is unprecedented in its intensity to overcome the changing challenges in the global market. A conceptual note has been developed to understand the boardroom challenges and the requirement of corporate stewards to combat the situation of health crises. The article discusses the new boardroom challenges the organization have to face such as virtual boardroom, right board composition, dynamic risk assessment, continuity and resilience. The need of the hour for corporate is to have an effective and steward board to overcome the health and financial challenges. The article also intends to give suggestions to the companies to manage the pandemic situation with a right steward attitude. Their diligent work can lead to increase in profits, which could further satisfy the shareholders with higher returns.